Comparison and intrinsic correlation analysis based on composition, microstructure and enzymatic hydrolysis of corn stover after different types of pretreatments. (December 2019) - Li, Junbao; Zhang, Haiyan; Lu, Minsheng; Han, Lujia
Graphical abstract: Highlights: Different types of pretreatments had various effects on properties of corn stover. Correlation analysis was conducted on properties of different pretreated corn stover. Content and exposure of cellulose had positive correlation on glucose yield. The destruction of spatial structure had positive correlation on glucose yield. Quantitative relationships between properties and glucose yield were established. Abstract: Pretreatment is a key step in the energy utilization of lignocellulosic biomass. Different types of pretreatments (ultrafine grinding pretreatment, alkaline hydroxide peroxide pretreatment, dilute acid pretreatment, and ammonia fiber expansion pretreatment) were conducted on corn stover. The lignocellulosic composition, microstructural parameters, and glucose yield of differently pretreated corn stover were characterized and compared. Then qualitative and quantitative correlation analyses of the parameters were carried out to explore the correlations among the composition, microstructure properties, and enzymatic hydrolysis efficacy of corn stover after different types of pretreatments and identify the main properties affecting enzymatic hydrolysis. Qualitative correlation analysis found that cellulose content, specific surface area, pore volume, enzyme-accessible pore volume, and surface area of cellulose had significant positive correlations with glucose yield. The results of quantitative correlation analysis were GY = 15.01 × cellulose content-339.05, GY = 13.06 × SSA + 172.35, GY = 7226.27 × PV + 129.14, GY = 8628.61 × EAPV + 125.61, and GY = 1.18 × SAC-287.21.